ON THE DISTRIBUTION OF ECHINOCOCCOSIS IN THE REPUBLIC OF KAZAKHSTAN (Experimental biology, 2022)
Echinococcosis is a zoonotic helminthiasis of humans and animals, caused by Echinococcus granulosus tapeworms. Treatment of echinococcosis is often expensive and complex and may require extensive surgery or long-term drug therapy. In addition, echinococcosis causes serious damage to livestock every year. At any given time in the world, more than 1 million people are affected by echinococcosis. Kazakhstan is among the countries unfavorable for echinococcosis. The purpose of this study is to establish the infection of sheep with cystic echinococcosis in the most endemic regions in the south and west of the country. In addition, to analyze statistical data on the incidence of human larvaceous echinococcosis in the Republic of Kazakhstan for 2020-2021. to assess the current situation on echinococcosis in the country. The situation with echinococcosis currently remains difficult. Echinococcosis is found in all regions of the republic, but the most endemic region is the south of Kazakhstan, which is a large livestock center. The highest rates of infection in sheep were found in the West Kazakhstan region and Almaty region - 16.7% and 12.52%. In terms of the incidence of people in the republic for a year and a half, 557 cases of larval echinococcosis have been identified. The highest rates are observed in Turkestan, Zhambyl, Almaty regions and in Shymkent. Echinococcosis is least common in Pavlodar, Kostanay regions and in the city of Nur-Sultan. The existing system of registration of patients with echinococcosis and statistical data do not fully reflect the real number of people infected with echinococcosis, since only surgical cases are taken into account. Monitoring of natural foci of echinococcosis is necessary, especially in the south, for coordinated disease control measures.
Keywords: echinococcosis, morbidity, sheep, cestoda, parasites, helminthiasis